Asymmetric Volatility of the Indian Stock Market and Foreign Portfolio Investments : An Empirical Study - Varughese, Ashish; Mathew, Tomy (Indian Journal of Finance, 2017)
Generally, a stock index may respond more to bad news (negative shocks) than to good news (positive shocks). It means stock market volatility may tend to be greater in a declining market than in a rising market. This behavior of stock return volatility is known as asymmetric volatility or leverage effect of volatility.Â  A healthy and vibrant capital market is important for economic development of a nation. In the present Indian scenario, stock prices inIndiafrequently deviate from fundamental values, and it is believed that these variations are mainly due to the presence of the most dominant investment group - foreign portfolio investors. This paperÂ  attempted to analyze the stock return volatility, especially the asymmetric effect of Indian stock market return volatility and contribution of foreign portfolio investment to that volatility. The present study was conducted by taking daily data for a period of 12 years fromApril 1, 2003toMarch 31, 2015consisting of 2898 trading observations. To study the leverage effect and impact of FPI on stock market volatility, the study used ARCH family models; GARCH, E-GARCH, and TARCH. The results of the study confirmed the existence of volatility clustering and leverage effect in the Indian stock market. Hence, it was observed from the study that the investment activities of FPIs have had a significant impact on the volatility of the Indian stock market.